Seronegative autoimmune hepatitis - A. O. Buyeverov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To summarize the modern data on the course, diagnostics and treatment approach in seronegative autoimmune hepatitis (SAH). Summary. The number of articles devoted to SAH is quite low at the present time, while all of them are based on the small case series or single cases. Absence of elevated serum γ-globulins, immunoglobulin G and autoantibodies is most commonly seen in acute onset of the disease that is probably caused by delay of humoral immune response of the disease. According to available information one can postulate following: 1) clinical vigilance for SAH, especially at liver diseases with high biochemical activity; 2) performing liver biopsies in all cases of unclear diagnosis; 3) application of standard scoring diagnostic system at autoimmune hepatitis; 4) prescription of immunosuppressive therapy at justified suspicion for SAH (at ruling out of the other causes for liver disease). Conclusion. SAH is a rare type of autoimmune hepatitis which is observed mostly at the acute onset of the disease and require obligatory morphological confirmation.